Hair cell regeneration from inner ear progenitors in the mammalian cochlea - Zhang, Shasha (Am J Stem Cells, 2020)
Cochlear hair cells (HCs) are the mechanoreceptors of the auditory system, and because these cells cannot be spontaneously regenerated in adult mammals, hearing loss due to HC damage is permanent. However, cochleae of neonatal mice harbor some progenitor cells that retain limited ability to give rise to new HCs in vivo. Here we review the regulatory factors, signaling pathways, and epigenetic factors that have been reported to play roles in HC regeneration in the neonatal mammalian cochlea.